1983
DOI: 10.1111/j.1744-6570.1983.tb01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Attribute Preferences and Work Commitment of Men and Women in the United States

Abstract: The extent of assumed sex differences in preferences for work attributes is explored utilizing data from five representative national samples. The results indicated only minimal differences in preferred job attributes between males and females. Both sexes identified meaningfulness of the work as the most important job attribute, and rank ordered the other four attributes studied in the following sequence: promotion, income, security, and hours. Factors such as education, occupational prestige, age and one's co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 30 publications
10
69
1
1
Order By: Relevance
“…On the other hand, Campbell (1976) reported that single men are less job satisfied than married men, but that no such difference exists for females. Lacy, Bokemeier and Shepard (1983) find no differences in the consequences of gender-specific childhood socialization for job satisfaction. Nor do they find that a wide range of job characteristics differentially affect the work attitudes of men and women.…”
Section: Background Of the Studymentioning
confidence: 74%
“…On the other hand, Campbell (1976) reported that single men are less job satisfied than married men, but that no such difference exists for females. Lacy, Bokemeier and Shepard (1983) find no differences in the consequences of gender-specific childhood socialization for job satisfaction. Nor do they find that a wide range of job characteristics differentially affect the work attitudes of men and women.…”
Section: Background Of the Studymentioning
confidence: 74%
“…Other researchers have found no relationship between gender and commitment (Aven, Parker & McEvoy, 1993;Blau & Boal, 1989;Cohen & Lowenberg, 1990;Kacmar & Carlson, 1999). Finally, other researchers have found that men are more committed than women (Graddick & Farr, 1983;Lacy, Bokemeier & Shepard, 1983;Mathieu & Hamel, 1989).…”
Section: Gendermentioning
confidence: 95%
“…Lee (1971) and Steers and Spencer (1977) have found these results to be inconsistent. Lacy et al (1983) found higher educated people to be more committed to work. Knoop (1986); Luthans et al (1987); Mannheim (1975); Newton and Keenan (1983) and Siegel and Ruh (1973) found a positive relationship between education and commitment.…”
Section: Educational Levelmentioning
confidence: 98%
See 1 more Smart Citation
“…We controlled for the effect of eight variables likely to influence the preference given to compensation components, including age (Bretz and Judge, 1994;Jurgensen, 1978;Lacy, Bokemeier, and Shepard, 1983;Zedeck, 1977), gender (Jurgensen, 1978;Konrad et al, 2000), work experience (Bretz and Judge, 1994;Feldman and Arnold, 1978;Zedeck, 1977), level of education (Jurgensen, 1978;Lacy, Bokemeier, and Shepard, 1983), organization size (Posner, 1981;Turban and Keon, 1993), salary, number of dependants, and organizational tenure (Lacy, Bokemeier, and Shepard, 1983).…”
Section: Control Variablesmentioning
confidence: 99%